Evolution of metallo-beta-lactamases in focus of the antibiotic resistance problem - Moskalov, Vitalii; Kadenko , Iryna; Mukhin , A.M. (My University, 2025)
The article considers the place of metallo-beta-lactamases among the mechanisms of antibiotic resistance. These enzymes have important differences from serine beta-lactamases, which affect the mechanism of their catalytic activity, inhibition, rate of spread and evolution. The history of the study and the social significance of antibiotic resistance in general and beta-lactamases in particular are described. The classifications of enzymes that hydrolyze the beta-lactam ring are presented, the structure of the reaction center of metallo-beta-lactamases and a hypothetical model of its functioning are described. Two fundamentally different mechanisms of inhibition of metallobeta-lactamases (zinc-dependent and zinc-independent) and their consequences for the development of therapeutic strategies are also considered. Metallo-beta-lactamases were distributed among non-pathogenic natural populations of bacteria, and then began to spread to pathogenic ones (initially gram-negative), which determines the importance of their study from the point of view of public health. The high rate of spread of these enzymes is due to their localization in structures such as integrons, insertion sequences and conjugation plasmids and can be illustrated by the example of the NDM enzyme, first isolated in New Delhi in 2009, which spread throughout the world in ten years and formed three dozen mutant variants. The fact that metallo-beta-lactamases arose in evolution twice is almost proven. Today, the phylogenetic relationships between different representatives of this enzyme family have been more precisely clarified and the presence of ten monophyletic groups has been established. The data presented in the article can serve as a starting point for planning comprehensive work on predicting the evolution of metallo-beta-lactamases, which carry serious risks for the treatment of infectious diseases.
Keywords: mechanisms of antibiotic resistance; molecular evolution of bacteria; molecular adaptations; механізми стійкості до антибіотиків; молекулярна еволюція бактерій; молекулярні адаптації